Financial Instability, Uncertainty and Bank Lending Behavior - Swamy, Vigneshwara; Sreejesh, S. (Universiti Utara Malaysia, 2012)
“Why do banks squeeze their lending activity” is an oft-repeated question during the times of financial crisis. This study examines an emerging economy’s banking system, and contributes to the evolving body of literature on the topic by providing answers to what causes the sluggish bank credit during times of recession. By employing cointegration technique, the study shows that bank credit has a significant positive relationship with the borrowing activities of debt users of the banks, hence, as the contrary an inverse relationship with investment activity is evident during financial crisis. Accordingly, we suggest that banks could increase their lending by increasing the borrowings rapidly either from the Central Banks or from Government supported long term lending institutions during recessionary periods.